2022
DOI: 10.1177/13591053221075503
|View full text |Cite
|
Sign up to set email alerts
|

Looking bad: Female patients drawing their representation of chemotherapy-induced alopecia

Abstract: This study explored the experienced impact of alopecia using patient’s drawings. Forty patients made drawings of their feelings about appearance of their head and hair before and during chemotherapy. Patients also reported illness perceptions (B-IPQ). Twenty-four patients (60%) reported ⩾50% alopecia at enrollment. Most patients (70%) drew a negative change of feelings over time and physical changes. Many experiences related to alopecia emerged from the written texts underneath the drawings and the B-IPQ. Draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…For example, attention was paid to the improvement of patients’ quality of life ( Bozcuk et al, 2017 ), reduction of pain ( Stinley et al, 2015 ), improvement of interpersonal relationships ( Durrani, 2019 ), improvement of psychological resilience ( Huss et al, 2012 ), and increased self-esteem, self-efficacy, and happiness ( Beauregard, 2014 ). A study ( Versluis et al, 2022 ) that investigated the hair loss experience and feelings of patients with cancer receiving chemotherapy based on negative emotions caused by hair loss through painting therapy suggested that medical practitioners should pay attention to and take measures against hair loss in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, attention was paid to the improvement of patients’ quality of life ( Bozcuk et al, 2017 ), reduction of pain ( Stinley et al, 2015 ), improvement of interpersonal relationships ( Durrani, 2019 ), improvement of psychological resilience ( Huss et al, 2012 ), and increased self-esteem, self-efficacy, and happiness ( Beauregard, 2014 ). A study ( Versluis et al, 2022 ) that investigated the hair loss experience and feelings of patients with cancer receiving chemotherapy based on negative emotions caused by hair loss through painting therapy suggested that medical practitioners should pay attention to and take measures against hair loss in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…A Dutch group studied the changes in body image of women undergoing chemotherapy, in particular the problem of hair loss [17][18][19] . These researchers observed that in designing their physical appearance, these women sought to represent themselves as deteriorated and sustained this image with expressions of negative feelings, revealing their difficulty in coping with esthetic changes to their bodies and consequently in presenting their female identity in the social world.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, a quantitative assessment of image perception and a qualitative evaluation of the experience suggested an advantage of the new device in comparison with the standard wig. In the literature, we found that patients were pleased with the wig in that it helps them maintain their normal appearance [ 7 , 28 , 29 ]. Nevertheless, Versluis et al [ 28 ] found that most patients felt a changed identity despite the use of a head covering.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, we found that patients were pleased with the wig in that it helps them maintain their normal appearance [ 7 , 28 , 29 ]. Nevertheless, Versluis et al [ 28 ] found that most patients felt a changed identity despite the use of a head covering.…”
Section: Discussionmentioning
confidence: 99%